The Radial Forearm Flap - P. A. Vinod Kumar; K. Kesavadev (Indian Journal of Plastic Surgery, 1988)
The radial forearm osteocutaneous flap is recently described single stage method for reconstruction of the thumb. The long term results of the two cases treated by us are being presented. The value of the procedure under Indian conditions has been discussed.